Synthesis and Biological Evaluation of Substituted Thiophenyl Derivatives of Indane-1, 3-Dione - D. Giles; M. S. Prakash; K. V. Ramseshu (E-Journal of Chemistry)
Indane-1, 3-dione (1) synthesized by condensation of diethyl phthalate and ethyl acetate in presence of sodium ethoxide gave sodium salt of ester derivative, which on neutralization in presence of sulphuric acid afford 1. Various thiols where converted to their respective disulphide (3) which on treatment with 1 gave 2-substituted thio phenyl derivatives (4a-g) of 1. The synthesized compounds were characterized on the basis of I.R and H1NMR. Synthesized compounds (4a-g) were investigated for their anticoagulant, analgesic, anti-inflammatory, antifungal, antibacterial and anticancer activities. Some of the synthesized compounds have shown moderate activities.